Terrorism, Human Capital Development and Economic growth in Nigeria - Oluwaseun B Alade; Ifeoma MBA; Ebikabowei Biedomo Aduku; Chika Anayochukwu Ameh (International Journal of Economics Development Research (IJEDR), 2021)
Terrorism in Nigeria is on the increase despite government counter-terrorism efforts and expenditure. This paper examines the impact of terrorism on economic growth and human capital development in Nigeria from 1981 – 2019. The Generalized Method of Moments (GMM) estimator was employed in analyzing the data. A negative and insignificant impact of terrorism on economic growth and human capital development was found. Internal and external conflict also had a negative and insignificant impact on economic growth and human capital development. Government expenditure as well had a negative and insignificant impact on economic growth and human capital development. Domestic investment had a positive and significant impact on economic growth, while its impact on human capital development was positive but insignificant. We, therefore, recommend establishing a bank of security to directly fund security in Nigeria. This can contribute to remedying the terrorism situation. Also, establishing a bank of security can serve as a channel where armed forces and other security personnel who died in service to the nation can be compensated. This will encourage the armed forces in the battle against terrorism.